Utilization of Cu-nanoparticles as medication agent to reduce atherosclerotic lesions of a bifurcated artery having compliant walls. (February 2020) - Shahzadi, Iqra; Suleman, Sana; Saleem, S.; Nadeem, S.
Highlights: As anticipated the fluid velocity show increasing behavior with the wall parameters Ei . The stresses on the outer wall of mild stenosed and bifurcated artery are inversely related with half the bifurcation angle α and is directly proportional to heat source parameter β. The stresses on the outer wall of arteries increases with an increase in wall parameters Ei ( i = 1, 2, 3). The trapping phenomena illustrates that more bolus appears for the larger Grashroff number. Abstract: Objective: A theoretical analysis is presented to study the bio-nanofluid with copper as medication agent for atherosclerotic bifurcated artery with flexible walls. Design/approach: The circulatory framework in human body is comprised of a system of veins that incorporate the bifurcation in this way the impact of copper nanoparticles on parent, at apex and on daughter artery regions (in the wake of being bifurcated) is watched. Streaming of blood along vessel segment is recognized to be newtonian. The consistent idea of the atherosclerotic arterial wall is additionally considered to make relationship with permeability aspects with arterial wall thickness. Copper nanoparticles are utilized to reduce the atherosclertic lesions for bifurcated stenotic artery. Findings: The designed equations along with the experimental values of copper nanoparticles and blood are utilized for theoretical investigation. Moreover, hemodynamics impacts are also figure out to examine the flow of blood for atherosclertic artery. Comparison between parent and daughter artery is plotted through velocity profile. To see the theoretical assistance of this copper mediated model in biomedical field, graphical illustration is presented. At the end, noticed that the inclusion of copper nanoparticles enhances the velocity significantly both for parent as well as daughter artery. Conclusions: The circulation of blood is considered to be different from pressure between portions of atherosclerotic and non-atherosclerotic artery. Shear stress is reduces by changing the bifurcation angle for daughter artery while trend is reversed for parent artery. The size of inner circularting bolus decreases by changing compliant parameter for parent artery while shape is changed for daughter artery. Graphical abstract: Image, graphical abstract